A framework for contextualising the formation and transformation of the medina in North Africa. (11th November 2019) - Abudib, Huyam Hadi; Remali, Adel Mohammad
Abstract : Purpose: The purpose of this paper is to offer a framework to contextualise the formation and transformation of three major medinas in North Africa, namely, Tripoli, Tunis and Fez. The framework is designed to identify key factors that formed these medinas in the first place, and key causes of transformation in reference to three distinctive forces: colonisation, modernisation and globalisation, which include political, economic and social changes that influenced the transformation process. Design/methodology/approach: Colonisation, modernisation and globalisation changed the physical appearance and urban fabric, introduced new architectural styles and at the same time changed the social structure, lifestyle, and the inhabitants' perception and use of spaces within their medinas. Physical aspects of the transformation process are investigated using comparative case studies, while social aspects are studied through interviewing three main actors in housing: users, decision makers and professional architects. Findings: By identifying key factors of formation and main drivers of transformation, together with analysing the physical and social aspects associated with the transformation process, the framework aims at developing a holistic, complex picture of housing transformation within a specific context: the medinas of North Africa. However, the framework is introduced as a valuable tool for exploring the transformation of other cities with relevant and similar context. Originality/value: Through the use of comparative case studies and interviews, the study focuses on capturing the essence of traditional medinas, understanding the reality of social change within housing transformation and contextualising the physical aspects of housing transformation.